M&A Performance of European Banks: An event study analysis - Antoniadou, Maria Louiza (2019)
M&As in the European banking sector have been in the centre of heated debate due to their unique policy dimension and controversial arguments regarding their effect on the banks’ performance. This study investigates the impact of M&As on bank performance using a sample of 64 completed M&A deals that took place in the 28 EU members plus Norway and Switzerland between 2000 and 2018. The event study methodology was used to analyse the stock market reaction around the deal announcement for the bidders and the targets. Consistent with previous studies, the targets’ shareholders earned significantly positive returns around the announcement when their significance was tested using non-parametric tests. However, when the z-test was used to assess the magnitude of the abnormal returns they turned out to be insignificant. Furthermore, despite the common finding in the majority of US studies that bidders experience losses after the transaction announcement, the evidence indicates that bidders are not harmed but neither gain. Additionally, the effect of relative pre-merger profitability, relative size, geographic focus and method of payment on the short-term price effect was investigated using an Ordinary Least Squares multiple regression. Nevertheless, the effects were not robust enough to explain the variation in cumulative abnormal returns around the event.